Navigating Dividend Decisions: The Impact of Outsider CEOs in Imputation Tax Environments - Ariful Hoque; Md Rayhan Islam; Shahadat Hossain (Risks)
This study examines the influence of outsider CEOs on corporate dividend policies, specifically within the framework of an imputation tax environment, like in Australia. The study analyses 9826 firm-year observations from Australian firms listed on the ASX from 2012 to 2021. The study reveals that outsider CEOs tend to distribute lower dividend payouts; a trend observed even after robustness tests. Methodologically, the study addresses potential endogeneity issues through sophisticated methods like propensity score matching, difference-in-difference approach, and two-stage system generalized method of moments. The findings indicate that firms led by outsider CEOs, particularly those with specialized industry knowledge, are more inclined to invest undistributed profits in capital expenditure projects, reflecting an investment-oriented strategy. This research contributes significantly to understanding the strategic decision-making of outsider CEOs and their impact on dividend policies in specific tax environments.